2005
DOI: 10.1099/vir.0.81090-0
|View full text |Cite
|
Sign up to set email alerts
|

Ectromelia virus: the causative agent of mousepox

Abstract: Ectromelia virus (ECTV) is an orthopoxvirus whose natural host is the mouse; it is related closely to Variola virus, the causative agent of smallpox, and Monkeypox virus, the cause of an emerging zoonosis. The recent sequencing of its genome, along with an effective animal model, makes ECTV an attractive model for the study of poxvirus pathogenesis, antiviral and vaccine testing and viral immune and inflammatory responses. This review discusses the pathogenesis of mousepox, modulation of the immune response by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
175
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(179 citation statements)
references
References 146 publications
4
175
0
Order By: Relevance
“…1). 4 Uncontrolled viral replication leading to liver tissue destruction, necrosis, and apoptosis is a hallmark of mousepox (19,20,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 4 Uncontrolled viral replication leading to liver tissue destruction, necrosis, and apoptosis is a hallmark of mousepox (19,20,41).…”
Section: Discussionmentioning
confidence: 99%
“…Liver damage and liver failure, as a result of uncontrolled ECTV replication within the organ, are major reasons for mortality (19,20,41). In addition to effective activation of ECTV-specific CD8 ϩ effector T cells, recruitment of those cells into the sites of viral replication is also critical for limiting infection and disease.…”
Section: Reduced Cd8 ϩ T Cell Numbers In Foci Of Infection In the Absmentioning
confidence: 99%
“…In contrast, susceptible A, BALB/c, DBA and C3H mice often succumb to disease due to necrosis of the spleen and liver. Resistance to mousepox is associated with rmp (resistance to mousepox) genes and recovery from infection requires mobilization of cell-mediated and innate immune responses (Esteban and Buller 2005). Krzyżowska and colleagues (2002) showed that infection of BALB/c mice with a highly virulent Moscow strain of ECTV (ECTV-MOS) leads to DEVDase-(caspase-3-and caspase-7-) dependent apoptosis in the liver, spleen, conjunctivae and lymph nodes which, presumably, regulates the resolution of viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…108). Importantly, in comparison to the VACV-based mouse challenge model, ECTV infection of BALB/c or C57BL/6 mice is characterized by an extended asymptomatic incubation period.…”
Section: Animal Modelsmentioning
confidence: 99%